The Extent to Which Twenty-First Century Skills Are Included in Digital Skills Books for the Fourth Grade of Primary School in The Kingdom of Saudi Arabia - Alnufaei, Amani Muneer; Hakami, Ibtisam Ahmed; Almohammadi, Najwa Atyan (Journal of Curriculum and Teaching Methodology, 2023)
The study aimed to know the degree to including the twenty-first century skills in digital skills books for the fourth grade of primary school in the Kingdom of Saudi Arabia. To achieve the objectives of the study, the researchers followed the descriptive analytical approach in the manner of content analysis of its suitability for the nature of the research, where the researchers analyzed the content of digital skills books prescribed for the fourth grade students in the primary stage of the three semesters, for the course of the academic year 1443 AH- 2021 AD, using a content analysis card that includes (11 A major skill followed by (24) sub-skills and included (62) indicators to measure performance distributed in three main areas of the skills of the twenty-first century: learning and creativity skills, digital culture skills, work and life skills, and the results showed that the skills of the twenty-first century in books Digital skills were at a low rate of (33.33 (%;Life and vocational skills ranked first with a percentage of (47.67), learning and creativity skills came in the second place with a percentage of (46.03), while digital culture skills ranked third and experts with a percentage of (6.55). In light of the results of the study, the researchers recommended the development of digital skills decisions for the fourth grade of primary school in the Kingdom of Saudi Arabia in the light of the skills of the twenty-first century due to the importance of these skills in preparing an individual capable of facing the challenges that may face him.